First report of banana bunchy top virus in banana and plantain (Musa spp.) in Angola - Kumar, P. Lava; Ayodele, M.; Oben, T.T.; Mahungu, N.M.; Beed, Fenton D.; Coyne, Danny L.; Londa, L.; Mutunda, M.P.; Kiala, D.; Maruthi, M.N. (Wiley, 2009)
In April 2008 in the northern Provinces of Angola, banana (AAA genome)and plantain (AAB genome) plants (Musa spp.) with severe stunting andmoderate to severe leaf symptoms typical of banana bunchy top diseasewere observed to be widespread in farmers’ fields in Kirimadhola villagein the Ndalatando region in Cuanza Norte Province, and Tokosiala, Bukuli Tsiela and Conde villages in the Landana region of Cabinda Province.Leaf extracts from affected plants were positive in an ELISA assay(OD405nm of infected ≥ 2 × healthy controls) using a polyclonal antiserum(NCBR, India) raised against Banana bunchy top virus (BBTV; genusBabuvirus, family Nanoviridae). BBTV was further confirmed by PCRusing total DNA extracted from plant samples with symptoms andoligonucleotide primers specific for a ca. 250 bp conserved domain ofBBTV DNA-R, according to published PCR protocols (Mansoor et al.,2005). An amplicon of the expected size (256 bp) was cloned into pGEM-T Easy Vector (Promega) and two independent clones were sequencedin both directions (GenBank Acc. No. EU851977). Comparisons ofthis sequence using a blast search showed the greatest nucleotideidentity (97%) with a BBTV isolate from Hawaii (U18077) and 96 to 97%similarity with BBTV isolates of a ‘South Pacific Group’. By contrast,there was less similarity (85 to 90%) with isolates of the ‘Asian Group’,indicating that the virus isolate from Angola falls within the South PacificGroup.This is the first report of BBTV occurrence in Angola. Together with pre-vious reports of BBTV in southern and central African countries (Kenyonet al., 1997; CABI, 2005), this report provides evidence for the widespreadoccurrence of BBTV in the region. The presence of both the virus and itsaphid vector, Pentalonia nigronervosa, in Africa has the potential to causewidespread damage to banana, especially on the highly susceptible Caven-dish types. This highlights the urgent need for intensive surveys to assessthe extent of the geographic spread and severity of BBTV in Africa and theimplementation of phytosanitary measures to eradicate infected plants.